Histological features of osteoarthritic canine cartilage after prolonged administration of carprofen - Dassler, C. L.; Griffey, S. M.; Vasseur, P. B. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The objective of this study was to determine whether the non-steroidal anti-inflammatory drug (NSAID) carprofen causes adverse histological changes to cartilage after prolonged administration for treatment of naturally acquired osteoarthritis.Dogs diagnosed with cranial cruciate ligament rupture and secondary osteoarthritis of their stifle joints were divided into two groups: those who had received a standard dose of carprofen for a minimum of four weeks and those who had not received a NSAID for a minimum of one month. Cartilage from the intercondylar notch was obtained when the patients underwent surgical procedures to stabilize the stifle joint. The samples were processed and evaluated for histological differences using haematoxylin and eosin and safranin-O-fast green-iron haematoxylin stains and were graded according to a Mankin scale (graded 0-14) for osteoarthritis.The histopathological findings were variable and included loss of matrix staining, irregularities to the cartilage surface, matrix fragmentation, chondrocyte clustering, matrix degeneration and vascular and synovial invasion (pannus) and were not specific to either group. There was not any significant difference between study groups (p = 0.2721) according to the Wilcoxan rank sum test.
Keywords: Carprofen; osteoarthritis; cartilage; non-steroidal antiinflammatory drugs